Issues of professional training of sports journalists - Duisebay Д.; Taspolatova Р. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article discusses the history of Kazakhstani sports journalism, analyzes the history of its occurrence and the text processing skills of famous sports commentators. The article discusses the concepts of «sports commentator» and «sport», «sports journalism», «Kazakh sports journalism» in the minds of Kazakhs. The concepts of “sport” and “sports journalism” became known in the years when the Soviet Union became part of the Soviet Union. During the reign of Russia in Russia - Ivan Poddubny, of the Kazakhs - Kazhymukan Munaytpasov played historical reality in the world. Russian sports columnist links Mayak to the World Union of Christian Youth (Youth and Youth), founded in St. Petersburg in the 1900s. It was created by American writer John Stokes. This organization existed before the Soviet Union. His main goal was to teach youth physical education. Kazakhstani society was formed together with the Soviet Union and its widespread idea of socialism. It is clear that the term sports journalism originated in Russia in the terms “Soviet sport”, “physical education and sport” and “sport” in two languages in Kazakhstan. In this article, the authors talk about the development, problems and prospects of Kazakhstan sports journalism